2000
DOI: 10.1093/intimm/12.9.1329
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and chemokines are both expressed by human myoblasts: possible relevance for the immune pathogenesis of muscle inflammation.

Abstract: The idiopathic inflammatory myopathies are characterized by antibody- or cell-mediated immune response against unknown muscle tissue antigens. In these diseases a cellular infiltrate, composed of T and B lymphocytes, macrophages and NK cells, may invade muscle tissue with a gradient from the perivascular space to the endomysial compartment. Muscle cells may be actively involved in the processes of mononuclear cell recruitment and activation from the blood stream to the areas of inflammation. In order to verify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
138
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(159 citation statements)
references
References 24 publications
19
138
1
Order By: Relevance
“…Although one study reported a modest infiltration of lymphocytes (3), subsequent histologic studies have failed to demonstrate interstitial infiltration of inflammatory cells in PMR. Interestingly, other studies have shown that the cytokines measured in the present study are released from myoblasts and fibroblasts (38). Furthermore, in response to exercise, IL-6 may be released from myocytes and interstitial fibroblasts (39,40), and IL-8 may be released from myocytes (41).…”
Section: Discussionsupporting
confidence: 44%
“…Although one study reported a modest infiltration of lymphocytes (3), subsequent histologic studies have failed to demonstrate interstitial infiltration of inflammatory cells in PMR. Interestingly, other studies have shown that the cytokines measured in the present study are released from myoblasts and fibroblasts (38). Furthermore, in response to exercise, IL-6 may be released from myocytes and interstitial fibroblasts (39,40), and IL-8 may be released from myocytes (41).…”
Section: Discussionsupporting
confidence: 44%
“…50 In human myoblasts, the induction of membrane and soluble ICAM-1 expression can be downregulated by TGF-b and IL-10, suggesting that these two cytokines can attain their inhibitory effect, influencing the ongoing inflammatory process in muscle, through modulation of adhesion molecules (Figure 2b). 51 Chemokine expression in inflammatory myopathies, 38 along with experimental in vitro results showing the effect of different cytokines on chemokine profile in myoblasts, confirms the importance of muscle cells in local leukocyte recruitment: 40 myoblast stimulation with IL-1b, IFN-g and TNF-a induces, with distinct kinetics, expression of the neutrophil-attracting IL-8, as well as of MCP-1, MIP-1a, MIP-3a and RANTES, acting mainly on lymphocytes and monocytes. Among these chemokines, IL-8 has a relatively unique and important role, as it is produced in the early stages of the inflammatory response, but it persists for a prolonged period of time, even for days and weeks; 52 this kinetics distinguishes it from most of the other (Figure 3a).…”
Section: Muscle Cells Recruit Leukocytesmentioning
confidence: 67%
“…Mouse CX3CR1 lo /Ly-6C + MOs and their human analogues bear several chemokine receptors, including CC chemokine receptor (CCR) 2, CCR1, CCR4, CCR7, CXC chemokine receptor 1, and CXC chemokine receptor 2 (9). The corresponding chemokines are expressed by muscle tissue during the fi rst days after injury (the cytokine expression profi le is available at http://pepr .cnmcresearch.org) (22,49,50). Monocyte chemoattractant protein-1 has been particularly involved in MO recruitment by injured muscle (19,20).…”
Section: Discussionmentioning
confidence: 99%